Assessment of medication adherence in patients at high risk of cardiovascular diseases - Pal, P. R.; Jat, Rakesh Kumar; Pal, Pooja Rajesh (Innovative Journal of Medical and Health Sciences, 2020)
BACKGROUND: Adherence to chronic pharmacotherapy is poor. Medication adherence is an important health issue. To better understand its relevance among vulnerable populations requires the availability of a valid, reliable and practical measurement approach. Researchers have proposed various competing methods, including pill counts and self-report measures. Medication adherence has been defined as the extent to which patients take medications as prescribed by their healthcare providers. Poor medication adherence diminishes the health benefits of pharmacotherapy. Elderly patients with coronary risk factors frequently require treatment with multiple medications, placing them at increased risk for nonadherence. OBJECTIVES: To test the efficacy of a comprehensive pharmacy care program to improve Medication adherence and its associated effects on blood pressure (BP) and low density lipoprotein cholesterol (LDL-C). METHODS: Prospective, Observational cohort study, in this study improvement in medication adherence & its associated effects on the patients before & after pharmacist involvement (intervention) was observed. Pharmacy records are reviewed, medication adherence was measured by proportion of days covered. PDC<80% was classified as poor adherence.( New York Heart Association )Group A- Hypertension (Usual group),Group B-Hyperlipidemia Intervention group (Pharmacist involvement) After a 2-month run-in phase (measurement of baseline adherence, BP, and LDL-C), patients entered a 6-month intervention phase (standardized medication education, regular follow-up by pharmacists, and medications dispensed in time specific packs). Following the intervention phase, patients were randomized to continued pharmacy care vs usual care for an additional 6 months. RESULTS: A total of 200 elderly patients with maximum lying in the age group 60-70 years, taking more than four chronic medications were enrolled. Coronary risk factors included drug-treated hypertension in102 patients (91.5%) and drug-treated hyperlipidemia in 99 patients (80.6%). Baseline medication adherence was 61.33% in usual care group and 70.44%.After 6 months of intervention, medication adherence increased to 72.22% in usual care and78.86% in pharmacy care group and was associated with significant improvements in BP and LDL-C . Two months after randomization, the persistence of medication adherence decreased to69.1%among those patients assigned to usual care, whereas it was sustained at 85.66% in pharmacy care. This was associated with significant reductions in systolic BP in the pharmacy care group vs the usual care group, but no significant between group differences in LDL-C levels or reductions. Conclusions: A pharmacy care program led to increases in medication adherence, medication persistence, and clinically meaningful reductions in BP and LDL level whereas discontinuation of the program was associated with decreased medication adherence and persistence. Key Words: S